Longitudinal evaluation of olfactory function in individuals with Gaucher disease and GBA1 mutation carriers with and without Parkinson's disease - Lopez, Grisel J.; Lichtenberg, Jens; Tayebi, Nahid; Ryan, Emory; Lecker, Abigail L.; Sidransky, Ellen (Frontiers in Neurology, 2022)
Objective Biallelic mutations in GBA1, which encodes the lysosomal enzyme glucocerebrosidase, cause the lysosomal storage disorder Gaucher disease (GD). In addition, mutations in GBA1 are the most common genetic risk factor for future development of Parkinson's disease (PD). However, most mutation carriers will never develop parkinsonism. Olfactory dysfunction is often a prodromal symptom in patients with PD, appearing many years prior to motor dysfunction. The purpose of this study was to assess olfactory function longitudinally in individuals with and without parkinsonism who carry at least one GBA1 mutation. Methods One hundred seventeen individuals who participated in a natural history study of GD at the National Institutes of Health were evaluated using the University of Pennsylvania Smell Identification Test (UPSIT) during a 16-year period. Seventy patients with GD (13 with PD) and 47 GBA1 carriers (9 with PD) were included. Fifty-six of the total (47.9%) were seen over multiple visits, and had UPSIT screening performed two to six times, with time intervals between testing ranging from 2 to 6 years. Comparative and control data were obtained from the Parkinson's Progression Markers Initiative (PPMI) database (519 individuals, including 340 with idiopathic PD and 179 healthy controls). Statistical analysis was performed using R. Results Severe hyposmia and anosmia was evident in both GBA1 heterozygotes and homozygotes with PD. 84% without parkinsonism had UPSIT scores >30, and those who underwent repeated testing maintained olfactory function over time. No statistically significant difference in UPSIT scores was found between mutation carriers with and without a family history of parkinsonism. A small group of individuals without PD scored in the moderate-severe microsmia range. No significant differences in olfaction were found among our GBA1-PD cohort and idiopathic PD cohort obtained from PPMI.